Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1089/jam.2000.13.231
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid in Cultured Ovine Tracheal Cells and Its Effect on Ciliary Beat Frequency In Vitro

Abstract: Hyaluronic acid (hyaluronan, or HA) is secreted by submucosal glands, but its function in airway secretions other than influencing the rheology of mucus is not fully understood. HA is known to modulate cell behavior and to enhance sperm motility. Because sperm tails and cilia have the same microtubular structure, we studied the effect of HA on ciliary beat frequency (CBF) in vitro. CBF of cultured ovine airway epithelial cells was measured continuously by digital video microscopy. After removal of endogenous H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 19 publications
5
27
0
Order By: Relevance
“…Although RHAMM was unregulated under gonadotropins, possible functions of this HA receptor in the bovine reproductive tract could be important, because basic expression levels during IVM were found to be compared to CD44 expression. The RHAMM may mediate movement and attachment of human cumulus cells [46], or it could modulate ciliary beating of oviduct epithelia, as described for the respiratory system [30]. Recent work discovered CD44 as the essential HA receptor throughout development of the preimplantation human embryo [47] and during trophoblast implantation [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although RHAMM was unregulated under gonadotropins, possible functions of this HA receptor in the bovine reproductive tract could be important, because basic expression levels during IVM were found to be compared to CD44 expression. The RHAMM may mediate movement and attachment of human cumulus cells [46], or it could modulate ciliary beating of oviduct epithelia, as described for the respiratory system [30]. Recent work discovered CD44 as the essential HA receptor throughout development of the preimplantation human embryo [47] and during trophoblast implantation [48].…”
Section: Discussionmentioning
confidence: 99%
“…Known to promote cell movement, RHAMM is located both in the cell as well as at the cell surface [27]. Furthermore, the HA receptor may be involved in wound healing [28], migration of smooth muscle cells [29], and modulation of ciliary beating of the airway epithelial cells [30].…”
Section: Introductionmentioning
confidence: 99%
“…This concentration of anti-RHAMM antibody inhibited locomotion of smooth muscle cells (24). The cells were then exposed within 60 min to hyaluronan (Seikagaku or Worthington; see Results; both with an average molecular mass of 200 kDa) at 50 g/ml, previously demonstrated to increase CBF (10). As a control, the cells were exposed to 20 M ATP to ascertain their response to a known stimulator of CBF.…”
Section: Measurement Of Cbfmentioning
confidence: 99%
“…We have previously shown that TK from broncho-alveolar lavage is bound to secreted hyaluronan that regulates its activity (4). We have also shown that ciliated cells in culture bind endogenously produced hyaluronan and that exogenously applied hyaluronan can stimulate ciliary beat frequency (CBF) (10).…”
mentioning
confidence: 99%
“…Hyaluronan plays a major role in mucosal defence because it increases the ciliary beat frequency of tracheal epithelial cells [40,41] . It is a constituent of human airway secretions and is produced mostly by ciliated surface epithelial cells, with some contributed by submucosal glands [42][43][44] .…”
Section: Discussionmentioning
confidence: 99%